Effect of different doses of sodium ortho vandate supplementation on DNA and sialic acid in rats - Ibrahim, A. L.; El-Ghannam, A. A.; Shalaby, Abeer A.; Bahr, Hoda I. (2011)
The present study was conducted to investigate the biochemical effect of low and high doses of sodium ortho- vandate supplementation on some blood and organ parameters in rats. The experimental study was carried out on 63 adult male rats weighing 150-200 gm. Rats were randomly divided into three equal groups each one comprised 21 rats and classified as follow: Group I (control group), group II (low dose of sodium ortho-vanadate group received 0.2 mg/ml sodium chloride solution 80 roM) and group III (high dose of sodium ortho-vanadate group received 0.6 mg/ml sodium chloride solution 80 mM) via drinking water. Blood samples and tissue specimens were collected after 2, 4 and 6 weeks from the onset of sodium ortho-vanadate supplementation. The obtained results revealed that a reduction (p< 0.05) in serum total sialic acid (TSA) concentration and the percentage of liver DNA fragmentation were observed after 4 and 6 weeks of low dose of sodium ortho-vanadate, 0.2 mg/ml (VLD) administration as compared with control. Meanwhile a marked increase (p< 0.05) in TSA and percentage of liver, heart DNA fragmentation were recorded after administration of sodium ortho vandate at high dose, 0.6 mg/ml (VHD) al1 over the period of the experiment. In addition, an elevation in heart and liver DNA content and reduction in the percentage of heart DNA fragmentation were observed after 6 weeks in VLD- treated group. From the obtained results it could be concluded that, low dose of sodium ortho-vanadate has antioxidant and antiapoptotic effect, while high dose of sodium ortho-vanadate has prooxidant and apoptotic effect. Key words: sodium ortho-vanadate, dose, oxidative stress, DNA, sialic acid, rats.
Includes references.
Summary in Arabic.
1
Keywords: Sialic acids -- Physiological effect; Animal models in research; DNA damage; sodium orthophenylphenoxide